Distribution of TNF-Î± Among Antenatal Women with Varying Levels of Vitamin D - Kashyap, Bineeta; Goyal, Nisha; Gupta, Neha; Jhanjhria, Sapna; Tajuddin, Mohd; Singh, NP (Annals of Pathology and Laboratory Medicine, 2019)
Background and objective: Vitamin D deficiency in antenatal mothers adversely affects not only the health of pregnant mother but also her child. Vitamin D is crucial for proper immune system functioning and management of cytokine environment. Relationship between vitamin D deficiency and TNF-Î± may prove useful in early detection of inflammatory conditions in pregnant mothers. Therefore, this study assessed serum vitamin D and TNF-Î± levels in antenatal mothers. Materials & Methods: 78 serum samples of healthy pregnant mothers were included. Serum 25-OH Vitamin D and TNF-Î± levels were estimated using commercially available ELISA kits. Results:25-OH Vitamin D levels were inadequate (<32ng/ml) in 94.9% of antenatal cases. Majority (74.4%)had an insufficient (11-32 ng/ml)25-OH Vitamin D level. Mean and median vitamin D levels were 16 Â± 7.5 SD and 14.5 ng/ml (3.5-39.5) respectively in antenatal mothers. None or a very weak positive linear relationship was observed between serum 25-OH Vitamin D and TNF-Î± levels (r: 0.13). No correlation was seen between 25-OH Vitamin D & age and TNF-Î± & age (r: 0.04; r: 0.06 respectively). Conclusions: In settings where subnormal vitamin D levels are prevalent in antenatal mothers, screening for vitamin D deficiency in early pregnancy with subsequent supplementation if needed is recommended. No correlation was observed between serum vitamin D and pro-inflammatory marker TNF-Î± levels. Further elaborate studies are required to investigate the effects of vitamin D on cytokine environment especially in pregnant mothers.